Pharmacology of α‐spinasterol, a phytosterol with nutraceutical values: A review. (8th July 2022) - Majeed, Muhammed; Ahmad, Furkan; Mundkur, Lakshmi; Appian, Subramoniam
Abstract: α‐Spinasterol is a phytosterol found in various edible and non‐edible plant sources. The edible plant materials containing α‐spinasterol include spinach leaves, cucumber fruits, seeds of pumpkin and watermelon, argan seed oil, cactus pear seed oil and Amaranthus sp. It is a bioavailable nutraceutical, and it can cross the blood–brain barrier. It possesses several important pharmacological properties such as anti‐diabetes mellitus, antiinflammation, hypolipidemic, antiulcer, neuroprotection, anti‐pain and antitumour activities. For this review, literature search was made focusing on the pharmacological properties of α‐spinasterol using PubMed and Google Scholar data bases. Recent studies show the promising antidiabetic properties of α‐spinasterol. Its anti‐diabetic mechanisms include enhancement of insulin secretion, reduction in insulin resistance, anti‐diabetic nephropathy, increase in glucose uptake in muscle cells and inhibition of glucose absorption from intestine. Besides, it is a safe antiinflammatory agent, and its antiinflammatory mechanisms include inhibition of cyclooxygenases, antagonism of TRPV1 receptor and attenuation of proinflammatory cytokines and mediators. It is a promising and safe nutraceutical molecule for human health care. Food supplements, value‐added products and nutraceutical formulations can be developed with α‐spinasterol for the management of diabetes, chronic inflammatory diseases and improving general health. This review provides all scattered pharmacological studies on α‐spinasterol in one place and highlights its immense value for human health care.